High‐Quality‐Factor Mid‐Infrared Toroidal Excitation in Folded 3D Metamaterials. Issue 17 (22nd February 2017) - Liu, Zhe; Du, Shuo; Cui, Ajuan; Li, Zhancheng; Fan, Yuancheng; Chen, Shuqi; Li, Wuxia; Li, Junjie; Gu, Changzhi
Abstract : With unusual electromagnetic radiation properties and great application potentials, optical toroidal moments have received increasing interest in recent years. 3D metamaterials composed of split ring resonators with specific orientations in micro‐/nanoscale are a perfect choice for toroidal moment realization in optical frequency considering the excellent magnetic confinement and quality factor, which, unfortunately, are currently beyond the reach of existing micro‐/nanofabrication techniques. Here, a 3D toroidal metamaterial operating in mid‐infrared region constructed by metal patterns and dielectric frameworks is designed, by which high‐quality‐factor toroidal resonance is observed experimentally. The toroidal dipole excitation is confirmed numerically and further demonstrated by phase analysis. Furthermore, the far‐field radiation intensity of the excited toroidal dipoles can be adjusted to be predominant among other multipoles by just tuning the incident angle. The related processing method expands the capability of focused ion beam folding technologies greatly, especially in 3D metamaterial fabrication, showing great flexibility and nanoscale controllability on structure size, position, and orientation. Abstract : A 3D toroidal metamaterial is fabricated by an ion beam induced folding technique on suspended SiN x film with metal patterns with well controlled split direction and spatial orientation. High‐quality‐factor toroidal moments are excited in the mid‐infrared region. The radiation power of the toroidal dipole in the far‐field is predominant compared to other dipoles by tuning the incident angle.